Omega 3 Supplementation Improves Inflammation and Antioxidant Defense in Women with Polycystic Ovary Syndrome - Benharrat, Latifa I.; Senouci, Azzeddine; Benhabib, Wassila; Mekki, Khedidja (Current Nutrition & Food Science, 2022)
Background: Polycystic ovary syndrome (PCOS) is the most common female endocrine disorder and is accompanied by metabolic syndrome (MS), a risk factor for cardiovascular disorders. Objective: To evaluate the effect of Omega 3 on the improvement of some metabolic parameters. Materials/methods: Sixty women (29±6 years) with PCOS and MS were randomized into two groups: 30 received supplementation with omega-3 (Doppelherz, Activ, Germany), 3g/day (1g per capsule and 3 capsules/day), (180mg Eicosapentaenoic Acid (EPA)/ 120mg Docosahexaenoic Acid DHA per day), and 30 were used as controls. Blood samples were drawn at baseline (T0), 3 weeks (T1) and 6 weeks (T2) after start of treatment. We analysed glycemia, lipid profile, markers of inflammation and oxidative stress. Results: In omega-3 group compared to control, a reduction (p<0.05) in glucose levels was noted at T1 and T2. C-reactive protein (CRP) concentrations were decreased (-25%) at T2. Oxidative stress remain unchanged, but the activity of superoxide dismutase increased as well as the concentrations of Catalase and thiols at T1 and T2 (p<0.001). Conclusion: Omega 3 supplementation improves hyperglycemia, inflammation, and antioxidant defense in PCOS women with MS, and may lead to decreased cardiovascular complications.
Keywords: Omega 3